Processing and Characterization of Al-4Cu Matrix Composites Reinforced with Few Layered Graphene - Kaykilarli, Cantekin; Kucukelyas, Burak; Akcamli, Nazli; Uzunsoy, Deniz; Cansever, Nurhan (SPRINGER INDIA, 2022)
Few-layered-graphene (FLG)-reinforced Al-4 wt.% Cu matrix composites were produced via the powder metallurgy (PM). FLG was incorporated into the matrix via a mechanical alloying (MA) process conducted for 5, 7 and 9 h in a planetary ball mill. The mechanically alloyed (MA'ed) powders were consolidated by uniaxial pressing and pressureless sintering. Properties of the Al-4Cu-xFLG composites were examined via Differential Scanning Calorimetry (DSC), X-ray Diffraction (XRD), Optical Microscopy (OM), Scanning Electron Microscopy (SEM), Energy Dispersive X-Ray Spectroscopy (EDX), Archimedes method, microhardness, compressive and wear tests. According to the mechanical characterization, FLG addition relatively improved the hardness, whereas it caused the decline of compressive strength. However, the specific wear ratio of the same sample increased by two times compared to the Al-4Cu.
Keywords: Al-Cu matrix composites; Graphene; Powder metallurgy; Mechanical and tribological properties; Metallurgy & Metallurgical Engineering